Cities' Identity Through Architecture and Arts : Proceedings of the International Conference on Cities' Identity Through Architecture and Arts (CITAA 2017), May 11-13, 2017, Cairo, Egypt. - Catalani, Anna. (CRC Press LLC, 2018)
Every city has its unique and valuable identity, this identity is revealed through its physical and visual form, it is seen through the eyes of its residents and users. Architecture and Arts is the embodiment of the cultural, historical, and economical characteristics of the city. This conference is dedicated for the investigation of the different new approaches developed in Architecture and Contemporary arts. It will focus on the basis of urban life and identities and discuss the examples and tendencies in dealing with urban identities as well as the transformation of cities and urban cultures mentioned in terms of their form, identity, and their current art.